2017
DOI: 10.1007/s10853-017-1094-6
|View full text |Cite
|
Sign up to set email alerts
|

Randomly oriented Ni–P/nanofiber/nanotube composite prepared by electrolessly plated nickel–phosphorus alloys for fuel cell applications

Abstract: In this work, we have synthesized a new type of hybridized composites, Ni-P/ CNT-CNFs, which refers to carbon nanotube (CNT)-hybridized carbon nanofibers (CNFs) through electrolessly plated nickel-phosphorus (Ni-P) alloys. The composites combine the merits of CNTs with high electronic conductivity and CNFs with abundant defect sites via the junction of electrolessly deposited Ni-P. The materials have been extensively characterized by scanning electron microscope, transmission electron microscopy, X-ray diffrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The distributed CNFs were sensitised and activated in SnCl 2 and PdCl 2 solutions at room temperature, respectively [30]. The pretreated CNFs were then filtered and thoroughly washed in distilled water [31].…”
Section: Methodsmentioning
confidence: 99%
“…The distributed CNFs were sensitised and activated in SnCl 2 and PdCl 2 solutions at room temperature, respectively [30]. The pretreated CNFs were then filtered and thoroughly washed in distilled water [31].…”
Section: Methodsmentioning
confidence: 99%
“…Figure 2C shows the strengthening efficiency of CNT in Al-CNT composites as a function of CNT content (Jagannatham et al, 2020). (Wu et al, 2017). Experiments showed that this irregularly oriented hybrid material, in addition to being an ideal candidate for non-precious metal electrocatalyst carriers, exhibited satisfactory ORR activity and excellent methanol tolerance in alkaline solutions.…”
Section: Usementioning
confidence: 99%
“…The highest conversion of 99.8% was achieved under appropriate reaction conditions, which indicates the high catalytic activity of MWCNTs/Ni-B nanoparticles ( Liu et al, 2011 ). Wu et al grew CNFs on CNTs by chemically plating Ni-P alloy in order to synthesize Ni-P/CNT-CNFs composites, which were directly used as electrocatalysts in methanol-resistant redox reactions (ORR) ( Wu et al, 2017 ). Experiments showed that this irregularly oriented hybrid material, in addition to being an ideal candidate for non-precious metal electrocatalyst carriers, exhibited satisfactory ORR activity and excellent methanol tolerance in alkaline solutions.…”
Section: Application Of Carbon Nanotubes After Electroless Platingmentioning
confidence: 99%
“…Previous studies reported that MWCNTs have an electrochemical activity toward oxygen reduction reaction (ORR) in both acidic and alkaline conditions. [35][36][37][38][39][40] Hence, this electrode was designed to work as a cathode for ORR and to be exible and foldable freely. Moreover, this paper electrode plays as a role of a reservoir for an electrolyte injected to the reserve battery.…”
Section: Introductionmentioning
confidence: 99%